(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
The development of the tahfidz Quran program nowadays can be said to be very rapid. The intensive tahfidz Quran program is an educational initiative to help students memorize the Quran in a more focused manner. This research aims to find out how the tahfidz program is implemented in improving students’ memorization at SMP N 6, Kapur IX District. This research used a descriptive qualitative research method with research informants, namely 2 Islamic Religious Education teachers, one accompanying teacher and 20 students. Data collection was carried out by observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and conclusions, data validity techniques use source triangulation and technical triangulation. The results of this research are that the implementation of the tahfidz program at SMP N 6 Kapur IX District is going well, where the implementation is carried out 2 days a week, namely on Friday and Saturday. In implementing the tahfidz program, students have a target of memorizing 1 juz in one year. The method used by teachers in the tahfidz learning process is the muroja’ah method with the media used, namely the Al-Quran and speakers. However, its implementation cannot be separated from the existence of supporting and inhibiting factors. Supporting factors in implementing the tahfidz program are the motivation of parents and teachers as well as facilities and infrastructure, while the inhibiting factors are students’ laziness, students who are not fluent in their reading, and difficulty dividing their time.